SISTEM PENDUKUNG KEPUTUSAN PENILAIAN KINERJA DOKTER MENGGUNAKAN METODE WEIGHT PRODUCT (WP) BERBASIS WEB - Junifa, Dira; Aisyah, Siti; Simanjuntak, Angelina Cikita Mutiara; Ginting, Syahril (Jurnal Sistem Informasi dan Ilmu Komputer, 2019)
The doctor is someone who because of his knowledge tries to heal people who are sick. One effort to spur doctors' performance is by conducting a performance evaluation. At present the job evaluation system at Royal Prima Medan Hospital is still done conventionally and the results of the assessment are subjective. Based on this, the author designed a Decision Support System for Evaluating Doctor Performance using WEB-based Weighted Product (WP). There are five criteria in evaluating doctor's performance including assessment of patient care, interpersonal and communication skills, writing and completeness of medical records, professionalism / work behavior. The research was conducted by looking for the weight values of the criteria and then processing the ranking from the doctor's judgment. Keywords: Decision Support System, Weight Product, WEB